Factors Related to Breastfeeding Success in Post-Partum Mothers: A Quantitative Approach in the Context of Applied Health Sciences - Nanik Yuliwati; Lia Kamalia; Vina Monica; Bela Tsuwwaebatul; Aas Mandasari; Dina Pani Mei Rizki; Adelia Mardiana; Dwi Putri Septini; Hikmatun Nazilah; Salsa Billa Romadhona (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to identify these factors in the context of health science education, particularly in the applied health sciences and maternal and child health. The study adopts a quantitative approach using a cross-sectional design. The study population includes postpartum mothers at Harapan Mulia Hospital in Bekasi (83 post-cesarean section mothers), Pondokgede District General Hospital (35 post-cesarean section mothers), and TPMB Lia Kamalia (35 normal postpartum mothers). Research instruments included structured questionnaires, observations of breastfeeding techniques, and interviews. Bivariate analysis was performed using the Chi-Square test, with a significance level of p <0.05. The results revealed that most mothers had good knowledge (62.9%), good nutrition (62.7%), were not at risk (73.3%), had a complete ANC history (66.7%), received good family support (60%), had good healthcare support (69.8%), adopted a healthy lifestyle (77.4%), practiced Early Breastfeeding Initiation (94.3%), and used correct breastfeeding techniques (85.7%). All these factors were significantly associated with breastfeeding success (p value < 0.05). Multivariate analysis using multiple logistic regression indicated that the dominant factors contributing to breastfeeding success were good breastfeeding technique (OR = 20.1; p = 0.004), Early Breastfeeding Initiation (EBI) (OR = 9.56; p = 0.045), and healthcare support (OR = 8.15; p = 0.001). This study underscores the need for comprehensive education and promotion of exclusive breastfeeding, emphasizing its significance in health science education. A holistic approach, including family-based interventions and strengthening maternal health literacy in the context of applied health sciences, is essential for enhancing breastfeeding success, particularly for mothers post-cesarean section. This research contributes to the improvement of maternal and child health services and the advancement of health science education in the context of midwifery services